Tree Ferns of C. contaminans and C. orientalis from Biosite Erek-erek Geoforest of Ijen Geopark, Banyuwangi - Ulum, Fuad Bahrul; Setyati, Dwi (BERKALA SAINSTEK, 2022)
The tree ferns abundant in the ecotourism area of the geoforest erek-erek biosite is represented as ancient plants. However, species list and their composition as diversity richness data is still lacking the in the conservation area. The aims of of this study was to determine the tree ferns and provide the description of the species. Observations on the morphological characters of plants were carried out directly in the field of tree ferns habitat at the Ijen geopark, Banyuwangi, while other morphological and anatomical determinations were conducted in laboratory. The tree ferns identified in the erek-erek forest were two species i.e., Cyathea contaminans and Cyathea orientalis. The main distinguishing characteristics of these species are: stem height, stem surface, attachment of the remaining petiole, scale color, crozier size, indusium and spore shape. This article also provides descriptions of the species and the information regarding conspicuous characters that can be used for species determination in the field. We also propose further conservation efforts to preserve the tree ferns in their habitat.